Adapting the TAM 3 Framework for Mandatory Performance Reporting Systems: A Study of ASN Teachers - Aljauhari, Moh Ali; Zakarijah, Masduki (International Journal of Technology and Education Research, 2025)
Focusing on educators within the Bandung Raya area, this research identifies the primary drivers behind the adoption and practical utilization of the mandatory Tunjangan Remunerasi Kinerja (TRK) digital platform. Positioned within the gap of limited empirical studies on mandatory e-government systems in education, this research employs an adapted TAM 3 framework. A quantitative approach was used with 321 ASN teachers as respondents, and data were analyzed using PLS-SEM via SmartPLS. The results show that the model explains 65.1% of the variance in Behavioral Intention and 49.3% in Actual Use. Ten of the fifteen hypotheses were supported. Perceived Usefulness (β=0.660) is the strongest predictor of intention, significantly higher than Perceived Ease of Use (β=0.197). Key antecedents such as Computer Self-Efficacy, Image, and Job Relevance are significant drivers, while Subjective Norm, Output Quality, and Result Demonstrability were rejected. The study’s novelty lies in proving that in mandatory contexts, users prioritize functional utility and professional image over social pressure or technical output quality. This suggests that government interventions should focus on increasing user efficacy and aligning system features with core teaching duties to ensure sustainable digital transformation.